2000
DOI: 10.1109/4234.892193
|View full text |Cite
|
Sign up to set email alerts
|

Simulation results for an interference-limited multiple-input multiple-output cellular system

Abstract: We describe a simulation study of a cellular system using multiple-input multiple-output (MIMO) antenna techniques along with adaptive modulation and aggressive frequency reuse. We show, for the case of 3 transmit and 3 receive antennas, how much MIMO systems outperform systems with receive-diversity-only when noise dominates. When co-channel interference from surrounding cells dominates, the differences shrink, as do the absolute numbers. We quantify these reductions for the specific cases studied, and discus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
68
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(68 citation statements)
references
References 7 publications
0
68
0
Order By: Relevance
“…In addition, transmission with only one antenna can eliminate practical issues such as mutual coupling, spatial correlation of antennas, and inaccurate time synchronization between antennas [22]. In the single AS scheme, K t = 1 and the ZF detector is similar to the SIC detector.…”
Section: Single-transmit Asmentioning
confidence: 99%
“…In addition, transmission with only one antenna can eliminate practical issues such as mutual coupling, spatial correlation of antennas, and inaccurate time synchronization between antennas [22]. In the single AS scheme, K t = 1 and the ZF detector is similar to the SIC detector.…”
Section: Single-transmit Asmentioning
confidence: 99%
“…MIMO systems offer dramatic data throughput gains over SIMO systems [4], and their basic properties and advantages have been thoroughly investigated by many authors. It has been shown that the incident field and the far field of the diversity antenna obey an orthogonality relationship, and the role of mutual coupling is central [5], while comparisons between spatial multiplexing schemes (SM) and diversity schemes via simulations revealed 6-12 dB higher SNR for diversity-based schemes, and 30-100% higher capacity for SM-based schemes [6].…”
Section: Introductionmentioning
confidence: 99%
“…single user) multi-input, multioutput (MIMO) links potentially can provide diversity and array gains for increased robustness as well as multiplexing gains for increased rate via appropriate space-time-frequency codes that map information symbols to frequency-time and antennas [13][14] [15]. However, in the presence of multiple access interference (MAI) in a spatial reuse scenario [6] [5], some degrees of MIMO design choice should be allocated to suppression of co-channel interference for higher link spectral efficiency [10]. Clearly, this implies a trade-off: transmit beamforming for downlink is used to mitigate the strong cochannel interferers at the reference receiver, thereby preserving a (nearly) interference-free link for the reference pair.…”
Section: Introductionmentioning
confidence: 99%